Upaya Meningkatkan Prestasi Belajar Siswa Melalui Pendekatan Pembelajaran Learning Community di Kelas VII SMPK Yos Sudarso - Sofia Sadhu (Program Studi Pendidikan Ekonomi, Universitas Flores, 2023)
This study aimed to increase students' achievement through the learning community approach in class VIII SMPK Yos Sudarso. Classroom action research was a research type. The data was gained through interviews and observation. The data were analyzed by using descriptive qualitative. The result showed the learning community approach could increase students learning achievement. It can be proved with the presentation of the pra cycle period achieved that the average was 63,33, and only 50% of students achieved a score 70 or >70, in enough categories. The learning result of the cycle I included learning increased the class grade to 69,89, and as many as 65% of students got scores complete in better categories. The lowest value was 50, and the higher was 90. The learning achievement of cycle 2 included learning achievement increased class grade became 83.3, and many 90% of students got complete scores in better categories. The lowest value was 70, and the highest value was 100. It can be concluded from this research found it has students' learning achievement increased. Based on the result, the learning community approach could increase students learning achievement.